Causal attributions of poverty: a social stratification analysis - Marquis, Lionel; Kuhn, Ursina; Tillmann, Robin (Frontiers in Sociology, 2025)
This study investigates the causal attributions of poverty among Swiss citizens using longitudinal data from the Swiss Household Panel (2019–2021). Agreement with the following four explanations of poverty was measured: “the poor are lazy” (individual blame), “the poor are unlucky” (individual fate), “the poor are victims of social injustice” (social blame) and “poverty is an inevitable consequence of the modern world” (social fate). Social blame shows the highest prevalence in Switzerland, followed by individual fate which has further increased over the COVID-19 pandemic. We focus on the relationship between poverty attributions and socio-economic stratification from a cross-sectional and dynamic perspective using pooled OLS and fixed effects models. The potential mechanisms discussed for individual and social blame involve self-interest, self-serving bias, socialization, exposure to poverty, resentment, and ideology. We take an encompassing view of social stratification, including education, income, wealth, deprivation, income mobility and social class. Our findings partially support the self-interest and self-serving bias mechanisms, with higher social positions correlating positively with individual blame attributions and negatively with social blame attribution. However, the socialization hypothesis is also supported, as higher education levels are associated with social blame attributions and poverty attributions do not react to changes in social stratification in the short term. Although poverty attributions vary relatively strongly within individuals over time, social stratification cannot explain intra-individual changes over time.